DICEPHALUS INIODYMUS MONSTER IN A CROSSBRED HF COW - KANTHARAJ, S; MURUGAVEL, K; SALAM, ABDUL; EZHILARASAN, C; RAJU, M S (The Indian Journal of Animal Reproduction, 2023)
This report describes a case of a live dicephalus iniodymus monster delivered pervaginally in a crossbredHF cow.
Keywords: Dicephalus; Bovine; Monster